ANALYSIS OF RISK TERMINAL FLOWS IN TECHNOGENIC SYSTEMS ARISING IN THE PROCESS OF THREAT IMPACT - Sabat, V. I.; Sikora, L. S.; Durnyak, B. V.; Povkhan, I. F.; Polishchuk, V. V. (Radio Electronics, Computer Science, Control, 2023)
Context. The analysis of the risk terminal flows in technogenic systems is carried out, which arise in the process of the impact of informational and cognitive threats in the automated document management system as part of the hierarchical production system. The object of the research is the process of functioning of complex systems with a hierarchical structure, in which automated document management systems with a high level of data flow protection for decision-making are used to provide the information quality control of technological processes. The subjects of the research are the methods and means of constructing an information protection system to ensure the reliable functioning of automated document management systems and making targeted decisions in hierarchical structures with minimal risk of exposure to external threats and attacks. Objective is to develop a complex model for assessing the risk of the document management system failure as part of a hierarchical production system under the active threats. Method. For the first time, the cause-and-effect diagram of the event formation with the active action of threat factors and attacks is substantiated and developed, the interpretation of risk in a technogenic system is defined, and the risk in the space of states is presented as a change in the trajectory in the system transitions to the limit operation mode. For the first time, a category diagram of the structure of risk generation under the threat factors and a system-category diagram of interaction in the system risk ↔ emergencyactive nature is constructed, a system-category scheme of risk formation under the active threat factors is suggested. For the first time, a cognitive diagram for assessing losses in the event of a risk situation arising from incorrect actions of the personnel is substantiated. Results. As a result of the research, a system-category diagram of the impact of a set of threats on the system functioning mode and process is constructed, a method is developed for calculating the level of system strategic security of energy-active hierarchical systems in the process of attacks and threats, and a complex model for assessing the risk of a system functioning failure under active threats is suggested. Conclusions. Under the action of active obstacles, cognitive and system factors at the operational and strategic levels of the control hierarchy, due to wrong decisions and informational disorientation, emergency situations and risks of the system function loss and its target-orientation arise. The analysis of a set of risks and the suggested category diagram of the risk generation structure under the impact of threat factors form the basis of the development of the probability structure of the risk concept based on the attack ↔ consequence model, as well as the construction of a system-category diagram of the interaction in the game active factor ↔ accident risk. This, in turn, makes it possible to construct a system-category scheme for the formation of risk terminal flows in technogenic systems that arise in the process of threat impact. A complex model for assessing the risk of system failure under threats can be used to construct protection systems for any hierarchical control structures of technogenic systems.